PENINGKATAN KEMAMPUAN MENULIS DENGAN TEKNIK MENULIS DARI GAMBAR OLEH SISWA KELAS XI SMK NEGERI 3 PADANGSIDIMPUAN - FAUZIAH NASUTION FAUZIAH NASUTION (Jurnal Education and Development, 2018)
This study aims to optimize the results of students' writing learning with writing techniques from pictures. This study uses a classroom action research approach (CAR). The research plan includes: 1). Action implementation, 2). Observation and analysis of results. This research was carried out in two cycles. First, write with traditional methods, second with writing techniques from pictures. The subjects of the study were students of class XI Busana SMK 3 state of Padangsidimpuan with a total of 43 people. The results of the study show that learning with techniques from images can improve students' ability to write significantly. This is evident during the learning process and the learning outcomes that have been done, where there is an increase in the ability of students to write through drawing techniques.